Incidence of occult leiomyosarcoma in presumed morcellation cases: a database study. (February 2016) - Rodriguez, Ana M.; Asoglu, Mehmet R.; Sak, Muhammet Erdal; Tan, Alai; Borahay, Mostafa A.; Kilic, Gokhan S.
Abstract: Objective: Our objective was to estimate the incidence of uterine leiomyosarcoma in patients with leiomyomas following laparoscopic supracervical hysterectomy and myomectomy procedures. Study design: For this study, we analyzed records of 13, 964 women aged 25–64 years who underwent laparoscopic supracervical hysterectomies or myomectomies for leiomyomas from 2002 to 2011 using Clinformatics DataMart. Patient records were divided into two groups: history of laparoscopic supracervical hysterectomy and history of myomectomy. Subjects were tracked to identify diagnosis of leiomyosarcoma within 1 year of the procedure. We analyzed data from the 25–39, 40–49, and 50–64 age brackets. Evidence was obtained from a cohort study from national private insurance claims in the US. Results: Our results showed the incidence of occult leiomyosarcoma developing within 1 year following supracervical hysterectomy using a laparoscopic-assisted approach are 9.8, 10.7, and 33.4 per 10, 000 for the 25–39, 40–49, and 50–64 age brackets, respectively; the overall incidence rate is 13.1 per 10, 000. The incidence rate of occult leiomyosarcoma developing within 1 year following myomectomy using a laparoscopic-assisted approach are 0.0, 33.8, and 90.1 per 10, 000 for the 25–39, 40–49, and 50–64 age brackets, respectively; the overall incidence rate is 17.3 per 10, 000. Conclusion: Our analysis shows the overall risk of being diagnosed with occult leiomyosarcoma is 12.9 per 10, 000 in laparoscopic-assisted supracervical hysterectomy and myomectomy for patients younger than 49. There is no evidence of occult leiomyosarcoma 1 year after operation for patients younger than 40 who underwent laparoscopic myomectomy.